2021
DOI: 10.1200/po.20.00468
|View full text |Cite
|
Sign up to set email alerts
|

Lung Cancer in Li-Fraumeni Syndrome

Abstract: Author affiliations and support information (if applicable) appear at the end of this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Previous reports revealed that patients with LFS and advanced lung cancer have a higher frequency of associated somatic mutations compared with the general NSCLC population, with EGFR mutation rates of 40% to 45%. 1 , 4 , 5 In one study, 90% of LFS-associated lung tumors (19 of 21) had somatic oncogenic drivers, in which 18 cases were EGFR -mutated with one patient having a ROS1 fusion. 5 In contrast to those with concurrent somatic TP53 and EGFR mutations, patients with germline TP53 and somatic EGFR mutations still benefit from EGFR TKIs, such as osimertinib.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous reports revealed that patients with LFS and advanced lung cancer have a higher frequency of associated somatic mutations compared with the general NSCLC population, with EGFR mutation rates of 40% to 45%. 1 , 4 , 5 In one study, 90% of LFS-associated lung tumors (19 of 21) had somatic oncogenic drivers, in which 18 cases were EGFR -mutated with one patient having a ROS1 fusion. 5 In contrast to those with concurrent somatic TP53 and EGFR mutations, patients with germline TP53 and somatic EGFR mutations still benefit from EGFR TKIs, such as osimertinib.…”
Section: Discussionmentioning
confidence: 99%
“…Germline mutations in the TP53 TSG are the defining feature of the cancer predisposition condition known as Li Fraumeni syndrome (LFS). 1 Lung cancer is a component of the LFS tumor spectrum with a risk of 2% to 7%, though the clinical phenotype of these lung cancers is not well described. 2 Though data are limited, most patients with LFS who develop lung cancer are younger and of the female sex, and reports describe a high incidence of somatic EGFR mutations, with an occurrence rate of up to 40% in one report.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TP53 is recognized to cause Li-Fraumeni syndrome, which causes an increased risk of lung and other cancers. 11,12 Other causal germline variants have been reported in a small number of lung cancer families, including in DICER1 13 ; SFTPA1 14 ; the T790M mutation in EGFR [15][16][17] ; HER2 18 ; BAP1 19 ; PARK2 20 and RGSI7. 21 Nevertheless, causal predisposition genes/variants have not been identified for the majority of lung cancer families studied.…”
Section: Introductionmentioning
confidence: 99%
“…Germline causal variants explain some familial lung cancer pedigrees. TP53 is recognized to cause Li‐Fraumeni syndrome, which causes an increased risk of lung and other cancers 11,12 . Other causal germline variants have been reported in a small number of lung cancer families, including in DICER1 13 ; SFTPA1 14 ; the T790M mutation in EGFR 15‐17 ; HER2 18 ; BAP1 19 ; PARK2 20 and RGSI7 21 .…”
Section: Introductionmentioning
confidence: 99%